Institutionalization risk and costs associated with agitation in Alzheimer's disease. Issue 1 (1st January 2019) - Cloutier, Martin; Gauthier‐Loiselle, Marjolaine; Gagnon‐Sanschagrin, Patrick; Guerin, Annie; Hartry, Ann; Baker, Ross A.; Duffy, Ruth; Gwin, Keva; Sanon Aigbogun, Myrlene; ,
Abstract: Introduction: Agitation in individuals with Alzheimer's disease (AD) may predict institutionalization. This study assessed the incremental risk and costs associated with agitation in individuals with AD. Methods: A retrospective analysis of the National Alzheimer's Coordinating Center Uniform Data Set (June 2005–February 2018) was conducted. Incremental risk of institutionalization associated with agitation was estimated and used with the number of institutionalized individuals with AD and agitation and costs of living by residential setting in the United States (literature‐based), to estimate incremental institutionalization costs. Results: The analysis included 11, 348 individuals with AD: 6603 (58.2%) with and 4745 (41.8%) without agitation. Compared with individuals without agitation, those with agitation were 20% more likely to be institutionalized (odds ratio = 1.20; 95% CI = 1.08–1.33). Total incremental cost of institutionalization associated with agitation was $4.3 billion ($50, 588/individual). Discussion: Agitation is associated with a higher risk of institutionalization among patients with AD, which translates into a substantial economic burden. Highlights: Agitation in Alzheimer's disease portends higher risk of institutionalization. Higher institutionalization risk translates into a substantial economic burden. Agitation‐related institutionalization cost was ∼$4.3 billion in the United States.